Upupianie Henryka, czyli NeKrošius inscenizuje Gombrowicza - Kopciński, Jacek (Załącznik Kulturoznawczy, 2018)
The subject of the essay is the staging of Gombrowicz’s Ślub [The Marriage], directed by Eimuntas Nekrošius at the National Theatre in Warsaw, treated as an example of ‘creative betrayal’ of the stage arranger towards the author of the dramatic text. ‘Creative betrayal’ is a perfect metaphor for directorial interpretation, which consists not so much in the stage materialisation of the fictional universe of the drama, as in the translation of the literary work’s meanings into the signs of a theatrical work. Referring to the theory of the spectacle as intersemiotic translation, the author shows how the stage world remains a creative reaction to the dramatic situations and conflicts designed by the playwright, as well as – to put it much more broadly – the image of a man and the shape of reality. According to the author of the essay, such a reaction as a rule contains polemic elements in relation to the playwright’s vision. Nekrošius remains polemical towards Gombrowicz, but his criticism – included in the actions of actors, scenography, costumes, and all directorial solutions – takes on a very deceitful shape. In his interpretation of The Marriage, the Lithuanian director focused on the motif and the problem of betrayal, which seems to be crucial in his worldview, based on psychoanalysis and existentialist philosophy. In this way, the stage arranger’s ‘betrayal’ became only an ironic response to the author’s ‘betrayal’, proving in fact ‘faithfulness’ to the meanings of the The Marriage, which was not noticed by the reviewers of the performance. Recalling the statements of one of them, author makes us aware of the complicated relationship between the author of a dramatic work, its director and the reviewer of the performance. And at the same time – of how typical for the dynamics of cultural life is the conflict between the participants of the artistic and critical dialogue.